If [tex]g(x)=\frac{2}{x} +3[/tex]
Find g(-3), this means that you need to find g(x) or y when x = -3.
[tex]g(x)=\frac{2}{x} +3[/tex] Substitute/plug in -3 into "x" since x = -3
[tex]g(-3)=\frac{2}{-3} +3[/tex] To combine fractions, they must have the same denominator. Multiply 3 by -3/-3 so that the denominators are the same.
[tex]g(-3)=\frac{2}{-3} +3(\frac{-3}{-3} )[/tex]
[tex]g(-3)=\frac{2}{-3} +\frac{-9}{-3}[/tex] Now combine the fractions
[tex]g(-3)=\frac{-7}{-3}[/tex] (two negative signs cancel each other out and become positive)
[tex]g(-3)=\frac{7}{3}[/tex]
If [tex]g(x)=\frac{2}{x+3}[/tex] , plug in -3 into "x"
[tex]g(-3)=\frac{2}{-3+3}[/tex]
[tex]g(-3)=\frac{2}{0}[/tex]
g(-3) = Undefined
When a number is divided by 0, the answer is undefined.